Implementasi Aplikasi Untuk Reservasi dan Rekam Medis dengan Menggunakan Metode Rapid Application Development Berbasis Mobile pada Klinik Yakrija - Noveindra Salim; Yolen Perdana Sari (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
Effective and efficient healthcare services are highly needed by the community, especially for clinics aiming to improve their service quality. Manual processes for reservations and medical record management are still widely found, often causing problems such as misplaced patient data, irregular queues, and service delays. This study aims to develop a mobile-based application to support integrated reservation and medical record management at Yakrija Clinic. The application was developed using the Rapid Application Development (RAD) method, enabling fast iterations according to user requirements. The implemented application facilitates patient registration, reservations, doctor schedule management, digital medical record documentation, as well as financial reports and transaction history. System testing shows that all main functions work well and are accepted by clinic users. It is expected that this application will improve efficiency, data accuracy, and patient satisfaction at Yakrija Clinic.